Improving the quality of future protein: an exploration of amino acid profile malleability in Fusarium venenatum - Szepe, Kamil J. (2024)
Meeting the food demand of a growing population whilst dealing the with effects of climate change is one of the biggest challenges facing humanity this century. The current food system is considered unsustainable, and alternatives are required to face the challenges. Some microorganisms can provide an alternative, sustainable and high quality source of dietary protein which, due to the organisms’ short generation times and general amenability to laboratory studies, also offers unique opportunities for improvement including by non-GM methods. The mycoprotein product from the fungus Fusarium venenatum has a high quality amino (AA) profile which, as shown here, is stable in different growth conditions. There was no significant difference in AA composition of F. venenatum cultured at industry or laboratory scale, supporting the extrapolation of laboratory-based experimental results to industrial production. The growth medium (RHM) used for industrial scale production of F. venenatum is not a prerequisite for the mycoprotein AA profile as culture of the fungus in different growth media did not change the AA profile and neither did substituting glucose with sucrose, an alternative carbon source. Supplementing cultures with agents that stimulate AA mis-incorporation (mistranslation) during protein synthesis by cells did not induce a detectable change to the AA profile of the fungus. High branch chained AA selection medium caused an enrichment in the AAs in the F. venenatum hydrolysate, but subsequent adaptive evolution experiments did not enhance the effect as intended. Furthermore AA (leucine) over-producing isolates of F. venenatum, selected via culture on the leucine derivative 5’5’5-tri-fluoro-leucine, showed no change in protein-AA profile despite up to a ~10 fold increase in free leucine. The stability of the F. venenatum AA profile supports the possibility of using alternative fermenter conditions and growth substrates (e.g. waste streams as components of the growth medium).